Case Study Of Mawe Tradition: The Theology Study Of Spirit Summoning Rituals In Buru Island, Maluku - Marisi, Candra Gunawan; Prasetya, Didimus Sutanto B; Tasijawa, Riski (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
Cultural traditions in Indonesia are very diverse, including the Mawe tradition on Buru Island, Maluku which is believed to be able to provide clues to uncover cases or problems that often occur. Uniquely, this tradition uses the spirits of deceased ancestors, which is a ritual led by traditional elders to provide clues that can explain a problem. This study uses a qualitative method with a case study approach and analysis of supporting Bible verses. As a result, from the theological studies conducted, it is known that rituals of seances have also been carried out in the biblical tradition, but it is clear that this tradition is contrary to the Bible. The Christian theological view is very clear that believers are not justified under any circumstances to perform seances because it is a form of syncretism.